2015
DOI: 10.1002/path.4546
|View full text |Cite
|
Sign up to set email alerts
|

Soluble factors regulated by epithelial–mesenchymal transition mediate tumour angiogenesis and myeloid cell recruitment

Abstract: Epithelial-to-mesenchymal transition (EMT) programs provide cancer cells with invasive and survival capacities that might favor metastatic dissemination. Whilst signaling cascades triggering EMT have been extensively studied, the impact of EMT on the crosstalk between tumor cells and the tumor microenvironment remains elusive. We aimed to identify EMT-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 76 publications
1
49
0
Order By: Relevance
“…Our finding that ZEB1 and ZEB2 are inducers of inflammatory cytokines is supported by a report by Suarez‐Carmona et al . (2015) that Slug, Snail, and other EMT‐related transcription factors regulate the production of soluble factors, such as IL‐8, IL‐6, sICAM‐1, PAI‐1, and GM‐CSF/CSF2. Taken together, these data indicate that inflammatory cytokines induce EMT‐related transcription factors and vice versa in certain cancer cells to enhance tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that ZEB1 and ZEB2 are inducers of inflammatory cytokines is supported by a report by Suarez‐Carmona et al . (2015) that Slug, Snail, and other EMT‐related transcription factors regulate the production of soluble factors, such as IL‐8, IL‐6, sICAM‐1, PAI‐1, and GM‐CSF/CSF2. Taken together, these data indicate that inflammatory cytokines induce EMT‐related transcription factors and vice versa in certain cancer cells to enhance tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR, Western blotting analyses, and flow cytometry qRT-PCR was performed as described previously (9). Primer sequences are provided in Supplementary Table S2.…”
Section: Sirna Transfectionmentioning
confidence: 99%
“…These transcription factors directly or indirectly repress or activate a variety of EMT target genes to provide cells with enhanced migratory and invasive ability, enhanced resistance to apoptosis and senescence, and proangiogenic and proinflammatory activities. While their repressive activity on several epithelial genes has been shown to involve a direct binding to promoter regions, their ability to induce mesenchymal genes rather implicates indirect and often unknown mechanisms (6)(7)(8)(9). Closely linking EMT to CTC, the expression of EMT mediators has been detected in CTCs in animal models (2,10) and in subpopulations of CTCs isolated from cancer patients including breast cancer patients, where they associate with poor clinical parameters and to the particularly aggressive "triple-negative breast cancer" (TNBC) subtype (5,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have now demonstrated that IL-8 can function in a paracrine or autocrine manner to affect the various cellular components of the TME. Functioning in a paracrine manner, for example, IL-8 released by cancer cells has been shown to promote the recruitment of various immune cell populations, mainly macrophages, neutrophils and suppressor cells of myeloid origin (see below), as well as to stimulate the angiogenic response in vascular endothelial cells leading to the formation of new blood vessels [39]. In addition, IL-8 released by tumor cells can function in an autocrine fashion to induce carcinoma cells to acquire a mesenchymal-like phenotype (i.e., induction of an EMT), as described in detail below.…”
Section: Tumor-driven Inflammation: Key Soluble Immune-mediatorsmentioning
confidence: 99%
“…Work conducted by Suarez-Carmona and colleagues [39] recently investigated the potential association between EMT and inflammation both in vitro and in vivo with xenograft models and with patient clinical samples. Similar to other studies, induction of EMT via epidermal growth factor (EGF)-treatment of TNBC lines resulted in a significant enhancement of secreted IL-6, IL-8, and other soluble factors.…”
Section: Emt Induces the Secretion Of Inflammatory Soluble Factorsmentioning
confidence: 99%